Kapabilitas Relationship Marketing Terhadap Kepuasan Nasabah Pada PT. Bank Rakyat Indonesia (PERSERO) TBK. Cabang Unit Peranap Kabupaten Indragiri Hulu - Reynaldo Septianda; Annisa Mardatillah (Pelantar Press, 2023)
This study aims to analyze the effect of relationship marketing on PT. Bank Rakyat Indonesia (Persero) Tbk. The Branch Office of the Peranap Unit as well as analyzing customer satisfaction at PT. Bank Rakyat Indonesia (Persero) Tbk. Peranap Unit Branch Office. This study also aims to analyze the effect of relationship marketing on customer satisfaction at PT. Bank Rakyat Indonesia (Persero) Tbk. Unit Branch Office). To determine the effect of these variables, relationship marketing indicators are used, which consist of trust, commitment, communication, and conflict handling. While the indicators used by the customer satisfaction variable consist of repurchase intentions, willingness to recommend, and confirmation of expectations. This research method uses a quantitative method with a descriptive approach. Data processing using data analysis techniques validity test, reliability test, simple linear regression test, t test (partial), and test the coefficient of determination (r) using the SPSS.25 application. Based on the tests conducted, the results obtained that relationship marketing affects customer satisfaction and the rest is influenced by other factors not observed in this study.